Orofacial antinociceptive activity of codeine-associated geraniol in mice: a controlled triple-blind study - Ana Paula Lopes NUNES; Humberto Hugo Nunes de ANDRADE; Danielle da Nóbrega ALVES; Gleycyelly Rodrigues ARAÚJO; Mirian Graciela da Silva Stiebbe SALVADORI; Reinaldo Nóbrega de ALMEIDA; Ricardo Dias de CASTRO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This is a nonclinical, controlled, and triple-blind study to investigate the effects of codeine-associated geraniol on the modulation of orofacial nociception and its potential central nervous system depressing effect in an animal model. The orofacial antinociceptive activity of geraniol in combination with codeine was assessed through the following tests: (i) formalin-induced pain, (ii) glutamate-induced pain, and (iii) capsaicin-induced pain. Six animals were equally distributed into six groups and received the following treatments, given intraperitoneally (i.p.) 30 minutes before the experiments: a) geraniol/codeine 50/30 mg/kg; b) geraniol/codeine 50/15 mg/kg; c) geraniol/codeine 50/7.5 mg/kg; d) geraniol 50 mg/kg; e) codeine 30 mg/kg (positive control); or f) 0.9% sodium chloride (negative control). We performed pain behavior analysis after the injection of formalin (20 µL, 20%), glutamate (20 µL, 25 µM), and capsaicin (20 µL, 2.5 µg) into the paranasal region. Rubbing time of the paranasal region by the hind or front paw was used as a parameter. In the neurogenic phase of the formalin test, the geraniol/codeine at 50/7.5 mg/kg was able to promote the maximum antinociceptive effect, reducing nociception by 71.9% (p < 0.0001). In the inflammatory phase of the formalin test, geraniol/codeine at 50/30 mg/kg significantly reduced orofacial nociception (p < 0.005). In the glutamate test, geraniol/codeine at 50/30 mg/kg reduced the rubbing time by 54.2% and reduced nociception in the capsaicin test by 66.7% (p < 0.005). Geraniol alone or in combination does not promote nonspecific depressing effects on the central nervous system. Based on our findings, we suggest the possible synergy between geraniol and codeine in the modulation of orofacial pain.